Bioactive terpenoid constituents from Eclipta prostrata. (February 2020) - Yu, Shu-Juan; Yu, Jin-Hai; Yu, Zhi-Pu; Yan, Xue; Zhang, Jun-Sheng; Sun, Jin-yue; Zhang, Hua
Abstract: Chemical fractionation of the ethanolic extract of Eclipta prostrata yielded a series of unreported terpenoid constituents, including a rare 6/6/6/6-fused tetracyclic triterpenoid, a pentacyclic triterpenoid, two pentacyclic triterpenoid saponins, a diterpenoid and a sesquiterpenoid. Structures were assigned to these compounds on the basis of comprehensive spectroscopic analyses, with the absolute configurations of the tetracyclic triterpenoid, the diterpenoid and the sesquiterpenoid being determined via explanation of electronic circular dichroism data. Screening of these isolates in an array of bioassays revealed antibacterial, cytotoxic and α -glucosidase inhibitory activities for selective compounds. Of particular interest, the tetracyclic triterpenoid showed very strong inhibition against α -glucosidase with an IC50 of 0.82 ± 0.18 μM, being 10 3 -fold as active as the positive control acarbose. Graphical abstract: Six unreported terpenoids including a rare 6/6/6/6 tetracyclic triterpenoid were isolated from Eclipta prostrata . Their antibacterial, cytotoxic and α -glucosidase inhibitory activities were evaluated. Image 1 Highlights: Six unreported terpenoid constituents were obtained from the aerial parts of Eclipta prostrata. Experimental and calculated ECD data were compared to establish absolute configurations. An oleanane-type triterpenoid saponin showed mild antibacterial activity against S. aureus. Two 28-noroleanane-type triterpenoid saponins showed cytotoxicity against two cancer cells. A rare lemmaphyllane-type triterpenoid displayed strong inhibition against α -glucosidase.